1993
DOI: 10.3109/00016489309135778
|View full text |Cite
|
Sign up to set email alerts
|

Postural Control and Age

Abstract: We quantified the effect of vision, pressoreceptor function and proprioception on the postural stability at different ages. Altogether 212 healthy volunteers (ages from 6 to 90 years) were examined by using a computerised force platform. The sway velocity (SV) was measured with eyes open and eyes closed during quiet stance on a bare platform and a foam plastic covered surface. In addition, to study the proprioceptive system, pseudorandom vibration perturbation was applied on the calf muscles. The SV showed a U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
4
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 20 publications
(6 reference statements)
15
106
4
4
Order By: Relevance
“…Much of our knowledge about the relationship between vision and balance has been obtained largely by comparing eyes open and closed conditions, and observing the effects upon body sway (Uchida et al 1979;Hytonen et al 1993;Fujita et al 2005;Rougier and Garin 2006;Guerraz and Bronstein 2008;Uchiyama and Demura 2008). While it has been shown that older adults sway more in response to unexpected eye-movements (Speers et al 2002;van Wegen et al 2002;Monzani et al 2005), the relationship between postural configuration and eyemovement behaviour is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Much of our knowledge about the relationship between vision and balance has been obtained largely by comparing eyes open and closed conditions, and observing the effects upon body sway (Uchida et al 1979;Hytonen et al 1993;Fujita et al 2005;Rougier and Garin 2006;Guerraz and Bronstein 2008;Uchiyama and Demura 2008). While it has been shown that older adults sway more in response to unexpected eye-movements (Speers et al 2002;van Wegen et al 2002;Monzani et al 2005), the relationship between postural configuration and eyemovement behaviour is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Giorgetti and colleagues 9) reported that FR may be a useful balance indicator in both healthy and impaired elderly subjects. SLS was adopted in this study to equalize the measurement conditions, shutting out visual information 17) . It has been incorporated into the Japanese standard of physical fitness by the Laboratory of Physical Fitness Standards 23) , and is considered to be highly reliable as a normal value of the balance function.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature [25][26][27][28], one can report that the stability of an individual deceases after 60 years old. When using the mPCA on rambling, two groups can be distinguished which is particularly interesting and promising.…”
Section: Age Effectsmentioning
confidence: 99%